åˆ©ç”¨å¯¹æ¯”æ•™å¦æ³•æé«˜å¦ç”Ÿå¯¹â€œåˆâ€å’Œâ€œå†â€çš„æŽŒæ¡èƒ½åŠ› - Florensia, Melvina; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦ ï¼šâ€œåˆâ€ å’Œ â€œå†â€ æ˜¯æ±‰è¯å£è¯å’Œä¹¦é¢è¯ä¸ç»å¸¸è€Œä¸”å¤§é‡ä½¿ç”¨çš„ä¸¤ä¸ªå‰¯è¯ï¼Œ ç”±äºŽæ„æ€ç›¸è¿‘ï¼Œå¯¹äºŽå¾ˆå¤šå¦ä¹ è€…æ¥è¯´ï¼Œâ€œåˆâ€ å’Œ â€œå†â€ åœ¨ä½¿ç”¨å’Œè¯ä¹‰è¾¨æžä»¥åŠå®ƒä»¬åœ¨å…·ä½“å¥åž‹ä¸Šçš„ä½¿ç”¨ä¸Šåˆæ˜¯å°¤ä¸ºå›°éš¾çš„ã€‚è™½ç„¶å‰¯è¯â€œåˆâ€å’Œâ€œå†â€èƒ½è‡ªç”±è¿ç”¨ï¼Œå¯æ˜¯å‰¯è¯â€œåˆâ€ å’Œâ€œå†â€ åœ¨è¯ä¹‰ï¼Œ è¯ä¹‰æŒ‡å‘æ–¹é¢æœ‰å¾ˆå¤§åŒºåˆ«ï¼Œç‰¹åˆ«æ˜¯å¯¹äºŽæ±‰è¯ä¸ºç¬¬äºŒè¯è¨€çš„å¦ä¹ è€…æ¥è¯´ï¼Œ è¿™ä¸¤ä¸ªå¾ˆéš¾åŒºåˆ«ã€‚ç¬”è€…åˆ©ç”¨å¯¹æ¯”æ•™å¦æ³•å¯¹ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦ä¸æ–‡ç³»2014å¹´Aççš„å¦ç”Ÿè¿›è¡Œå‰¯è¯â€œåˆâ€å’Œâ€œå†â€çš„æ•™å¦ã€‚ç›®çš„å°±æ˜¯ä¸ºäº†Â Â Â  æé«˜å¦ç”Ÿå¯¹å‰¯è¯â€œåˆâ€å’Œâ€œå†â€çš„ç†è§£ä»¥åŠæŽŒæ¡å¥½è¿ç”¨çš„èƒ½åŠ›ï¼ŒåŠ ä¸Šä½¿ç”¨æµ‹è¯•æ¥äº†è§£å¦ç”Ÿå¦ä¹ å‰å’Œå¦ä¹ åŽçš„æƒ…å†µå’Œç»“æžœï¼Œè¿›è¡Œå¯¹æ¯”ã€‚ç»“æžœå¾ˆæ˜Žæ˜¾å¦ä¹ åŽçš„ç»“æžœæ¯”å¦ä¹ å‰æœ‰æ‰€æé«˜ï¼Œè¿™è¡¨ç¤ºå¯¹æ¯”æ•™å¦æ³•é€‚åˆç”¨äºŽè¿›è¡Œå‰¯è¯â€œåˆâ€å’Œâ€œå†â€çš„æ•™å¦ã€‚ å…³é”®è¯ ï¼š å‰¯è¯â€œåˆâ€å’Œâ€œå†â€ å¯¹æ¯”æ•™å¦æ³• Abstract: "You" and "zai" are both common auxiliary verb that is often used in Chinese language in writing and speaking, since the meaning of those auxiliary verbs have similarities, for most people who learn it, "you" and "zai" in case of using and meaning of the words, and the using of those auxiliary verb in certain sentence could be very difficult. Even auxiliary verbs of "you" and "zai" can be used freely, however the auxiliary verb of "you" and "zai" in interpretation, in the aspect showing the meaning have a significant differences, especially for students who study Chinese Language as a second language, they will be very difficult to distinguish the auxiliary verbs.The author uses comparison method to teach the auxiliary verbs of "you" and "zai" to Chinese language education student of Tannjungpura University, class A of 2014. The purpose of the research is to increase studentsâ€™ understanding and to improve studentsâ€™ auxiliary verbs of â€œyouâ€ and â€œzaiâ€ mastery, including with giving the test to understand the condition and the results of the students before and after the treatment, and making a comparison. The result is very apparent that there has been increased after the treatment, it shows that the comparison method is suitable for teaching auxiliary verbs of "you" and "zai". Keywords: Adverbs â€œyouâ€ and â€œzaiâ€; Comparative Teaching Method